Exploring microgrid design and optimization using Homer Pro in Singapore - Lim, Li Ying (Nanyang Technological University, 2022)
Climate change is becoming such a big issue with the melting of icebergs, rise in sea level, and many other catastrophic environments related event going on due to the increase in carbon emission. One of the major contributors to carbon emission is power generation. Efforts have been made to help reduce carbon emission by increasing the usage of renewable energy to generate power. By using renewables, it is much cleaner compared to traditional power plant. However, to implement the use of renewable energy requires much planning and research to find the optimal system design for a certain location.